Alkali concentration and diluent effects on properties of grape cane fiber-reinforced polymer composites - A. Bakar, Balkis Fatomer; Kamke, Frederick A. (Multidisciplinary Digital Publishing Institute, 2021)
The main objective of this study was to investigate the properties of polymer composites reinforced with grape cane fibers. The fibers were subjected to a sodium hydroxide (NaOH) treatment at two treatment concentrations to extract the fibers as well as fiber surface treatment. Panels were fabricated by hand lay-up and compression molding according to different fiber types, namely outer bark (OB) and whole (W) fibers. The whole fiber was a mixture of OB and inner bark (IB) fibers. Grape cane fibers were used as the reinforcement material for unsaturated polyester (UPE) resin panels. Acrylated epoxidized soybean oil (AESO) was used as a reactive diluent material with the UPE resin, and the results were compared with panels prepared with commercial styrene–UPE. There were inconsistent alkali treatment concentration effects on the mechanical properties and water absorption. However, panels fabricated with the whole bark fibers that have been treated with 1 wt % NaOH and had AESO–UPE resin resulted in the best tensile and flexural strength.